The awakened ones: phenomenology of visionary experience - Obeyesekere, Gananath (Columbia University Press, 2012)
"Throughout his career, Obeyesekere has combined psychoanalysis and anthropology to illuminate the relationship between personal symbolism and religious experience. In this book, he begins with Buddha's visionary trances wherein, over the course of four hours, he witnesses hundreds of thousands of his past births and eons of world evolution, renewal, and disappearance. He then connects this fracturing of empirical and visionary time to the realm of space, considering the experience of a female Christian penitent, who stares devotedly at a tiny crucifix only to see the space around it expand to mirror Christ's suffering. Obeyesekere follows the unconscious motivations underlying rapture, the fantastical consumption of Christ's body and blood, and body mutilation and levitation, bridging medieval Catholicism and the movements of early modern thought as reflected in William Blake's artistic visions and poetic dreams. He develops the term 'dream-ego' through a discussion of visionary journeys, Carl Jung's and Sigmund Freud's scientific dreaming, and the cosmic and erotic dream-visions of New Age virtuosos, and he defines the parameters of a visionary mode of knowledge that provides a more elastic understanding of truth. A career-culminating work, this volume translates the epistemology of Hindu and Buddhist thinkers for western audiences while revitalizing western philosophical and scientific inquiry."--Jacket